PERSEPSI GURU PADA PENGINTEGRASIAN KEARIFAN LOKAL MELAYU RIAU DALAM MODUL AJAR IPS DI SDN 163 PEKANBARU - Indriani Barasa, Valensia; Erlisnawati; Zufriady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is driven by the Merdeka Curriculum policy emphasizing the integration of local wisdom to strengthen the Pancasila Student Profile, particularly nationalism. Although efforts exist to incorporate Riau Malay local wisdom in social studies (IPS) teaching, no in-depth studies explore teachers' perceptions of this process, necessitating an investigation into supporting and inhibiting factors at school. The study aims to reveal teachers' responses, impressions, and perceptions based on their experiences with integrating Riau Malay local wisdom into IPS teaching modules. It benefits module development for contextual relevance, student appreciation of Riau Malay culture, and researcher skill-building in writing. Employing a qualitative phenomenological approach, the research was conducted at SDN 163 Pekanbaru, an A-accredited school with 29 teachers and 552 students implementing the Merdeka Curriculum. Data were gathered via interviews (covering teaching experiences, perceptions, integration experiences, barriers, and supports), observations (internal: motivation, understanding, attitude, initiative; external: learning resources, school support, teacher involvement, classroom conditions; professional: development competency, active methods, evaluation, modules, ethics), and documentation (topics, objectives, media, references, worksheets, assessments, module coherence). Findings show teachers recognize integration's importance, drawing on Riau Malay elements like cuisine, proverbs, geography, and crafts. They exhibit strong motivation, understanding, positive attitudes, diverse resources (images, videos), and school support. Challenges include limited deep knowledge, inadequate training, scarce integrated modules, and minimal collaboration. Teachers hold positive perceptions but stress readiness considerations. Recommendations include specialized training, resource development, routine teacher discussions, and school cultural programs.